2023
DOI: 10.3390/medicina59050850
|View full text |Cite
|
Sign up to set email alerts
|

Biliary and Vascular Complications after Liver Transplantation–From Diagnosis to Treatment

Abstract: The last decades have brought impressive advances in liver transplantation. As a result, there was a notable rise in the number of liver transplants globally. Advances in surgical techniques, immunosuppressive therapies and radiologically guided treatments have led to an improvement in the prognosis of these patients. However, the risk of complications remains significant, and the management of liver transplant patients requires multidisciplinary teams. The most frequent and severe complications are biliary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…These masses are commonly associated with hepatic artery thrombosis. If the bile is already colonized by bacteria, bilomas become colonized as well, though they can also develop a secondary infection [ 16 , 17 ]. The diagnosis of bilomas is made with the aid of imaging techniques such as abdominal ultrasound, computed tomography (CT), or magnetic resonance imaging (MRI), as their signs and symptoms are usually nonspecific.…”
Section: Resultsmentioning
confidence: 99%
“…These masses are commonly associated with hepatic artery thrombosis. If the bile is already colonized by bacteria, bilomas become colonized as well, though they can also develop a secondary infection [ 16 , 17 ]. The diagnosis of bilomas is made with the aid of imaging techniques such as abdominal ultrasound, computed tomography (CT), or magnetic resonance imaging (MRI), as their signs and symptoms are usually nonspecific.…”
Section: Resultsmentioning
confidence: 99%
“…Entre las complicaciones vasculares, la trombosis de la arteria hepática es la complicación arterial más común y grave del trasplante de hígado, representando alrededor del 50 % de todas las complicaciones arteriales 7 , con una incidencia que varía del 0 % al 12 %. Es la principal causa de disfunción primaria del injerto hepático 7 .…”
Section: Discussionunclassified
“…Las complicaciones vasculares son menos frecuentes, pero con un pronóstico más incierto, con una incidencia que varía entre el 7-15 %, hasta alcanzar cifras del 25-30 % 3,6,7 . Se pueden clasificar en complicaciones vasculares oclusivas, como trombosis y estenosis 4,6 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Their findings indicated that DCD liver grafts did not exhibit an escalated risk of vascular stenosis in comparison to DBD [88]. Moreover, many studies reached the same conclusion [89,90]. Therefore, it remains to be determined if a marginally elevated rate of vascular complications can be expected when employing DCD donors with advanced age.…”
Section: Vascular Complicationsmentioning
confidence: 96%